Bury my heart at Chuck E. Cheese's - Midge, Tiffany, 1965- (University of Nebraska Press, 2019)
"Bury My Heart at Chuck E. Cheese's is a powerful and inviting collection of Tiffany Midge's musings on life, politics, and identity as a Native woman in modern America"--